Risk Management Analysis in Digital Bank XYZ Using the COBIT 2019 Framework - Purnomo, Rudi; Harwahyu, Ruki (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2025)
The digital transformation in the banking sector has driven the emergence of digital banks, offering online services without the need for physical branches. However, this transformation brings various risks, including information security threats and challenges in regulatory compliance. This study aims to evaluate the maturity level of risk management in Digital Bank XYZ using the COBIT 2019 framework. The research methodology employs a qualitative approach with gap analysis to compare the current state with expected standards. The findings reveal significant gaps in the APO13 (Managed Security) and DSS04 (Managed Continuity) domains between current risk management practices and the standards recommended by COBIT 2019. These results highlight the need for a more systematic and structured risk management approach to enhance Digital Bank XYZ's preparedness in addressing cybersecurity threats and other operational risks. Recommendations include strengthening security policies, implementing predictive technologies, and conducting regular training to improve the security team's competencies. This study is expected to serve as a strategic guideline for Digital Bank XYZ to mitigate risks, improve operational efficiency, and achieve international governance standards.